Hospitalizations due to sensitive conditions: the possibility of assessment in primary care - Ferreira, Marianna (2012)
Primary Care Sensitive Conditions (PCSC) are health problems treated using interventions typical of the primary healthcare level, which evolution caused be a lack of timely and effective care, may require hospitalization. This descriptive study was performed with the objective to analyze the occurrence of hospital admissions due to PCSC in the period spanning 2000 to 2007, among inhabitants of Ribeirão Preto – São Paulo. It is observed that after the implementation of the Family Health Strategy, there was a 9.6% reduction in hospital admissions by PCSC. However, significant increases were observed in groups such as Diseases Preventable by Immunization and Sensitive Conditions, and Anemia. This analysis suggests that despite the fact that public healthcare services in Ribeirão Preto promote interventions that prevent diseases and promote health, which appear to help reduce hospital admissions, there is and overall limited organization of the services, as there has been an increase in the number of admissions in groups with relevant diseases in the context of public healthcare service and nursing care. Descriptors: Community Health Nursing; Primary Health Care; Utilization; Hospitalization; Health Services Evaluation.